(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
In this research, focused on the environmental pollution from fuel combustions of automobiles, the study compared the maximum allowable limits for Iraqi emissions standard specification with the European emissions standard specification. Whereas many different between the Iraqi specification and European specification. The first one is limited unlike the second specification, which is dealt with all polluting gases, as well as differences in the measuring units between them. The Iraqi specification measures the emissions in ideal conditions while the European depends on the measurement on different operational conditions. This study was conducted on 35 automobiles, the emissions data was obtained by using an exhaust gas analyzer and represented by using a qualitative control tool ( - control charts); Minitab software version 2016 was used to generate quality control charts. Process capability index applied to measure the degree to which emissions meets the standard specifications. The results by control charts showed that about 30% of the automobiles emissions exceed the limits of the Iraqi standard specifications. This in turn affects negatively to the Iraqi environment, because emissions affect directly and indirectly to the environment and human health. Quality assurance requires continuous monitoring and Periodic inspections of automobiles to minimize and reduces harmful emissions from fuel combustion; therefore must be updated specification, as appropriate with the Iraqi environment.